Metode Markov Chain Untuk Prediksi Probing Terhadap Kinerja Promotor Pada Penjualan Oppo - Jani Kusanti; Tri Irianto Tjendrowasono (Infotekmesin, 2020)
Mobile promoters have their own way of attracting buyers during sale process. How promoters  attract buyers is called probing, probing expertise is needed by the promoter handphone. If the expertise is lacking then the prmoters will lose the opportunity to make maximum sales and vice versa. Therefore predictions are very important to make to find out whether the results of the promoter's performance on Oppo sales are affected by probing or not. This research was conducted by applying the Markov chain method, with the research object area of Amplas (Ambarukmo Plaza) Yogyakarta. The results showed that probing had a significant effect on sales but had less effect on sales targets, with a prediction rate of 35% has increased from sales results.